Education on Solar Cell Technology to Increase Clean Energy Literacy in Cileles Village, Sumedang - Mayang, Ajeng; Ardiansyah, Neris Peri; Barnadi, Yudi; Suryana, Ase (Institut Teknologi Nasional, Bandung, 2026)
Indonesia is in the process of transforming its energy system to reduce its dependence on fossil fuels and lower greenhouse gas emissions. This effort aligns with SDGs 7 and the national target of achieving a 23% share of renewable energy shared by 2025. However, low community energy literacy remains a significant obstacle, as seen in Cileles Village, Sumedang, which has considerable but underutilized solar energy potential. This community service program aimed to strengthen energy literacy and awareness of renewable energy by providing education on solar cell technology through a Participatory Action Research (PAR) approach. This activities included preparation, interactive learning, practical demonstrations using a solar cell model, and evaluation through pre- and post-tests. Implemented in August 2025 with 30 participants, the program successfully increased understanding of clean energy and encouraged interest in renewable energy adoption.